Can social communication be used as a strategy to enhance teaching and learning of life sciences? Perceptions of student teachers - Setlalentoa, Wendy (Department of Commnication Science, University of the Free State, 2012)
Social communication in the current context of an informational and technological society has become indispensable globally and in South Africa. This article examines how social communication can be used as a strategy to enhance teaching and learning of Life Sciences amongst student teachers at an institution of higher learning. Focus group discussions were held with senior Life Sciences student teachers, who were allowed an opportunity to tell their own stories of how they were able or unable to use social communication as it prevailed for them mediating the teaching and learning of Life Sciences. Social communication networks in education for example are increasingly used as a mode of delivery of education, but recently there have been some initiatives to establish how it can be used effectively in improving academic performance of students. Globally students are using social networks such as Twitter, MXit, Facebook, etc. although the majority of learners use this social means of communication for other purposes than education. The findings indicate that social communication enhances teaching and learning and regular usage thereof promotes learner interest in Life Sciences. Although there exists a strong desire to integrate social communication in the teaching of Life Sciences, there are many barriers. Accessibility, confidence and competence are critical components of technology; resources, effective professional development, and technical support need to be provided to student teachers.
Keywords: Social communication; Society; Life sciences; Education; Social networks; Social media